NÍVEIS TENSIONAIS SUGESTIVOS DE HAS E HÁBITOS DE VIDA ENTRE AGENTES UNIVERSITÁRIOS, GUARAPUAVA, PARANÁ , BRASIL - Bresan, Jessica Taís (2016)
Introduction: The decrease of the general and infant mortality rate, the increasing life expectancy of the population and the changing in the disease epidemiology profile were observed in Brazil over the past 50 years, with this change there was a progressive increase in Diseases and Non-Communicable Diseases (DNCDs) and a decrease in the occurrence of infectious diseases, providing a change in the population morbidity and mortality profile. Among the DNCDs, is that Systemic Arterial Hypertension (SAH) is a change in blood pressure ?140 value (systolic pressure) or ?90 (diastolic pressure), and hypertension is the most important risk factor for Cardiovascular Diseases (CVD). Objectives: To identify the prevalence of pressure levels suggestive of SAH, according to sociodemographic, behavioral and health-related in the population of university agents from Unicentro, Guarapuava, PR. Methods: This is a cross-sectional study conducted at the Universidade Estadual do Centro-Oeste (UNICENTRO), Cedeteg and Santa Cruz Campus, with university agents. Data collection was performed by applying structured interviews, anthropometric measurements and blood pressure measurement. Descriptive and analytical statistics of variables were performed, which were stratified by sex, using median and interquartile range for asymmetric numerical variables. Categorical variables were described by frequency and also stratified by sex. In analytical statistics to identify factors associated with hypertension were built Poisson regression models, obtaining prevalence ratios in uni and multivariate models, which were estimated by point and intervals with 95% confidence. Results: In the study sample, 26.3% of men and 28.3% of women had blood pressure levels suggestive of SAH, with 12 men and 10 woman were already using medication for hypertension. The age group with the highest prevalence of men and women with suggestive pressure levels of hypertension was 40-59 years. As for the educational level, 85.7% of men and 73.3% of women with suggestive pressure levels of hypertension had educational level of 12 years or more. The nutritional status of participants with hypertension was assessed as overweight in 57.1% of men and 66.7% of obesity in women. The waist circumference (WC) was considered at risk for CVD to 76.2% of men and 80.0% women with suggestive pressure levels of hypertension. Regarding the consumption of alcohol, 23.8% of men with suggestive pressure levels of hypertension showed dependence, while no women with suggestive pressure levels of SAH presented dependence. With regard to smoking, 38.1% of men and 20.0% of women with suggestive pressure levels of hypertension are former smokers. Alimentation has been assessed as regular by 71.4% of men and 80.0% of women with suggestive pressure levels of hypertension. In males, the variables that remain in the final model were smoking, working hours and length of marriage. Among females, the variables that remained in the final model were educational level and WC. Conclusions: The scenery found through the survey of the prevalence of suggestive pressure levels hypertension and its association with other cardiovascular risk factors made it possible to know the health profile of the studied university agents and thus realize that the obtained data reflect the social, economic, cultural and environmental changes, because it was found that both sociodemographic factors such as those related to health and behavioral are related with hypertension. Finally, while it is a small sample of university agents, it is noted that the prevalence of suggestive pressure levels of hypertension obtained is worrying and as in Brazil is a challenge for many sectors, it becomes an interdisciplinary problem, requiring the intervention of several areas and professions.